2020
DOI: 10.3389/fgene.2020.01011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Antibody Response to Porcine Reproductive and Respiratory Syndrome Vaccination as an Indicator Trait for Reproductive Performance in Commercial Sows

Abstract: We proposed to investigate the genomic basis of antibody response to porcine reproductive and respiratory syndrome (PRRS) virus (PRRSV) vaccination and its relationship to reproductive performance in non-PRRSV-infected commercial sows. Nine hundred and six F1 replacement gilts (139 ± 17 days old) from two commercial farms were vaccinated with a commercial modified live PRRSV vaccine. Blood samples were collected about 52 days after vaccination to measure antibody response to PRRSV as sample-to-positive (S/P) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(61 citation statements)
references
References 37 publications
5
56
0
Order By: Relevance
“…They reported greater AGP when using SNP within the two major QTL for Ab response to PRRSV on SSC7 (30 and 130 Mb) compared to the rest of the genome. Sanglard et al (2020) observed greater AGP for Ab response to PRRSV than in Serão et al (2016) in PRRSV-vaccinated gilts from the same population. Ab response to Newcastle disease and avian influenza in chickens was studied by Liu et al (2014), who reported moderate prediction accuracy for these traits.…”
Section: Genomic Prediction Accuraciesmentioning
confidence: 68%
See 2 more Smart Citations
“…They reported greater AGP when using SNP within the two major QTL for Ab response to PRRSV on SSC7 (30 and 130 Mb) compared to the rest of the genome. Sanglard et al (2020) observed greater AGP for Ab response to PRRSV than in Serão et al (2016) in PRRSV-vaccinated gilts from the same population. Ab response to Newcastle disease and avian influenza in chickens was studied by Liu et al (2014), who reported moderate prediction accuracy for these traits.…”
Section: Genomic Prediction Accuraciesmentioning
confidence: 68%
“…For instance, pigs selected for a higher immune response after 8 generations presented higher Ab response to various antigens and grew faster than pigs with a lower immune response (Mallard et al, 1998). For PRRSV, the major viral pathogen impacting swine production, moderate to high heritability (h 2 = 0.38-0.46) has been reported for Ab response to this disease in commercial gilts (Serão et al, 2016;Sanglard et al, 2020). Dunkelberger et al (2017) reported a high h 2 for PRRS viral load (0.61) but not for porcine circovirus type 2 (PCV2; 0.09).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total antibody response to porcine reproductive and respiratory syndrome ( PRRS ) virus ( PRRSV ), measured as sample-to-positive ( S/P ) ratio, has been proposed as an indicator trait for improved reproductive performance in PRRSV-exposed sows ( Serão et al, 2014 ; Sanglard et al, 2020 ). Following a PRRSV outbreak, Serão et al (2014) observed that S/P ratio had high heritability ( h 2 = 0.45) and high r g with reproductive performance in PRRSV-infected sows [0.73 ± 0.23 with number of born alive ( NBA )].…”
Section: Introductionmentioning
confidence: 99%
“…However, waiting for a PRRSV outbreak to happen for data collection limits the use of this indicator trait in pig breeding schemes. Sanglard et al (2020) investigated the use of S/P ratio to vaccination in commercial gilts as an effective strategy to continuously generating S/P ratio data in commercial settings. These authors reported a moderate h 2 (0.34 ± 0.05) and high r g of S/P ratio to modified live PRRSV vaccine with NBA (0.61 ± 0.16) in the absence of a PRRSV outbreak.…”
Section: Introductionmentioning
confidence: 99%